Assessing status of pests and diseases with cluster approach - A case of coconut in Kasaragod district in Northern Kerala - C. Thamban, K.P. Chandran; P.S. Prathibha, V.H. Prathibha (Journal of Plantation Crops, 2017)
The main objective of integrated pest and disease management is to intervene efficiently to reduce crop damage at minimum cost and inflicting minimum damage to the environment. The basic requirement for such programmes is the availability of a costeffective sampling method for assessing the status of incidence and intensity of the disease/pest attack wherein, accurate estimates is achieved through minimum efforts. In the present study, a sampling strategy and measures of severity and crop loss for simultaneous assessment of incidence of major pests and diseases of coconut were formulated and implemented in Kasaragod district of Kerala. The sampling methodology involved a cluster approach in which four clusters of at least 500 bearing palms from a minimum of ten coconut gardens, representing the geographical strata of the panchayath, were scored visually for the incidence of major pests and diseases. District level estimates were derived incorporating area under coconut in each panchayath as the weight. Information on geographic coordinates was recorded and utilized for preparation of thematic maps using Arc-GIS. Further, crop loss due to the major pests and diseases were also estimated under certain scenarios. The study revealed that diseases like stem bleeding and Thanjavur wilt were more prevalent in areas experiencing high temperature and low rainfall whereas, incidence of bud rot disease was significantly higher in hilly regions where low temperature and high humidity prevailed. Incidence of pests like eriophyid mite and coreid bug was higher in coastal areas of the district. The study could serve as a model for similar studies in future and the information emerging out of this study would help in formulating integrated pest and disease management programmes at grass root level.